Identifikasi Determinan Kepatuhan Kunjungan Posyandu Balita - Puput Risti Kusumaningrum; Endang Sawitri; Fitri Suciana; Nabila Amalia Inka Putri (TRIAGE Jurnal Ilmu Keperawatan, 2025)
The process of toddler growth and development is a crucial stage. This period greatly determines the success of the child's development in the future. Therefore, the involvement of mothers in posyandu activities is very important to monitor the growth and development of toddlers, reduce maternal and infant mortality, and expand the scope of basic health services. This study aims to describe various factors that influence the level of maternal compliance in bringing toddlers to posyandu in RW 2, Cawan Village, Jatinom, Klaten. This study uses a quantitative descriptive approach. The population in this study were all mothers of toddlers registered at Posyandu Lestari 2, totaling 60 people, with a sample size of 40 people selected using the accidental sampling technique. The research instrument was adapted from previous studies. The results showed that the average age of respondents was 31.5 years, all of whom were female. The majority of respondents (72.5%) had a high school/vocational high school education, and the majority (85.0%) were housewives. As many as 37.5% had one to two children, and 65.0% lived close to the posyandu location. Most respondents (95.0%) had high knowledge about posyandu. All respondents (100.0%) stated their support for toddler posyandu activities and felt they received support from health workers. In addition, 92.5% of respondents also felt supported by their families, and 72.5% considered that the facilities available at Posyandu Lestari 2 were adequate.Keyword: Factors, Compliance, Visits, Posyandu, Toddlers